2011
DOI: 10.1017/s0022112010006178
|View full text |Cite
|
Sign up to set email alerts
|

Gravity currents of carbon dioxide with residual gas trapping in a two-layered porous medium

Abstract: In the geological sequestration of carbon dioxide (CO2), residual gas trapping plays an important role in immobilizing CO2. In this study, we investigate the propagation of gravity currents with residual gas trapping in a two-layered porous medium. We first formulate a model for a constant-flux release of a relatively less dense fluid (CO2) from a point source into a porous medium bounded above by a horizontal less-permeable seal. After a constant-flux release ceases, a fraction of the released fluid remains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…Consistent with figure 2, it can be shown that for draining lengths significantly greater than the gravity current height, the direction of remains vertical and its length is given as . Taking these factors into consideration, the draining velocity can be written as In the limiting case when , (2.8) reverts back to the expression used in previous works (Goda & Sato 2011; Sahu & Flynn 2017).…”
Section: Theoretical Modellingsupporting
confidence: 61%
See 3 more Smart Citations
“…Consistent with figure 2, it can be shown that for draining lengths significantly greater than the gravity current height, the direction of remains vertical and its length is given as . Taking these factors into consideration, the draining velocity can be written as In the limiting case when , (2.8) reverts back to the expression used in previous works (Goda & Sato 2011; Sahu & Flynn 2017).…”
Section: Theoretical Modellingsupporting
confidence: 61%
“…. (ii) The upper and lower layers are assumed to be very deep in vertical extent (Goda & Sato 2011); the consequences of assuming otherwise will be briefly highlighted in § 4. (iii) Initially, the entire porous medium is assumed to be uniformly saturated with ambient fluid of density .…”
Section: Theoretical Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, gravity currents on an inclined surface have been studied by Vella & Huppert (2006) and Gunn & Woods (2011), or in a vertically confined medium by Nordbotten, Celia & Bachu (2005), MacMinn et al (2012), Pegler, Huppert & Neufeld (2014) and Zheng et al (2015). Moreover, by relaxing the restriction of a homogeneous medium, Pritchard, Woods & Hogg (2001), Goda & Sato (2011) and Sahu & Flynn (2017) have investigated gravity currents in layered porous media of differing permeabilities, while Zheng, Christov & Stone (2014) have investigated flow in horizontally heterogeneous medium. Formulations for modelling gravity currents in a highly heterogeneous medium have been presented by Anderson, McLaughlin & Miller (2003, 2004, who describe homogenization methods for the averaging of medium properties.…”
Section: Introductionmentioning
confidence: 99%